2017
DOI: 10.5194/os-2017-45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrography and Circulation West of Sardinia in June 2014

Abstract: Abstract. In the mainframe of the REP14-MED sea trial in June 2014, the hydrography and circulation west of Sardinia, observed by means of gliders, shipborne CTD instruments, towed devices, and vessel-mounted ADCPs, are presented and compared with previous knowledge. So far, the circulation is not well known in this area, and the hydrography is subject to long-term changes. Potential temperature, salinity, and potential density ranges, as well as core values of the observed water masses were determined. Modifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The rich dataset collected during the REP14-MED campaign is used for this purpose. REP14-MED took place in June 2014 off the western coast of Sardinia (Onken et al, 2018;Knoll et al, 2017). Two RVs tracked in parallel a 100× 100 km 2 area during a 20-day period, providing dense CTD sampling with a 10 km separation and continuous towed CTD measurements for limited periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…The rich dataset collected during the REP14-MED campaign is used for this purpose. REP14-MED took place in June 2014 off the western coast of Sardinia (Onken et al, 2018;Knoll et al, 2017). Two RVs tracked in parallel a 100× 100 km 2 area during a 20-day period, providing dense CTD sampling with a 10 km separation and continuous towed CTD measurements for limited periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter, the skill score decreased at a faster rate than in the global domain which indicated the reduced predictability in the more energetic regions. Ten years later in the framework of GODAE (Global Ocean Data Assimilation Experiment; Bell et al, 2009), Lellouche et al (2013) computed the skill score of the sea level anomaly forecast for different setups of the MERCA- TOR global model against persistence. They demonstrated that for most regions the skill score was positive, except for the North Atlantic, the Mediterranean Sea, and Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…exists (Knoll et al, 2017). SST increased by up to 0.6 • C between 19 and 20 March, and continued to increase intermittently to a maximum of 14.3 • C on 5 April (total increase of 1 • C over the deployment period).…”
Section: Development Of a Spring Bloommentioning
confidence: 95%